2013
DOI: 10.1136/heartjnl-2012-302925
|View full text |Cite
|
Sign up to set email alerts
|

South Asians and coronary disease: is there discordance between effects on incidence and prognosis?

Abstract: ObjectiveTo determine whether the effect of South Asian ethnicity differs between studies of incidence and prognosis of coronary disease.DesignSystematic literature review and meta-analysis, and cohort analysis from a national acute coronary syndrome (ACS) registry linked to mortality (National Institute of Cardiovascular Outcomes Research/Myocardial Infarction National Audit Project).SettingInternational for the review, and England and Wales for the cohort analysis.PatientsThe numbers of South Asians included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 43 publications
8
58
2
Order By: Relevance
“…35 Zaman and colleagues found that SA in the UK had a higher incidence of CAD but M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 paradoxically lower mortality once a diagnosis was made (HR 0.78, CI 0.74-0.82) and SA with DM had a better prognosis compared to Europids with DM. 20 Given the varying results, factors influencing prognosis following cardiac events in SA may be dependent on the specific population and country studied, perhaps changing over time and across nations. Specifically, SA ethnicity may not independently worsen CAD prognosis once the greater burden of DM is accounted for.…”
Section: Iii) Prognosismentioning
confidence: 99%
“…35 Zaman and colleagues found that SA in the UK had a higher incidence of CAD but M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 paradoxically lower mortality once a diagnosis was made (HR 0.78, CI 0.74-0.82) and SA with DM had a better prognosis compared to Europids with DM. 20 Given the varying results, factors influencing prognosis following cardiac events in SA may be dependent on the specific population and country studied, perhaps changing over time and across nations. Specifically, SA ethnicity may not independently worsen CAD prognosis once the greater burden of DM is accounted for.…”
Section: Iii) Prognosismentioning
confidence: 99%
“…Despite being identified as a major burden on health-care systems, there have been no large prospective cohort studies to define the incidence of coronary artery disease (CAD) among Indians. Therefore, the magnitude of the problem can only be estimated from cross-sectional point prevalence studies (3). Reports have shown that risk of CAD among Asian Indians is 3-4 times higher than white Americans, 6 times higher than Chinese, and 20 times higher than Japanese counterparts (4).…”
Section: Introductionmentioning
confidence: 99%
“…subarachnoid haemorrhage), the strength and shape of association of age with many CVDs varies substantially, and those of South Asian ethnicity experience substantially increased hazard of stable and unstable coronary presentations compared with white people 34,35 Estimates of national and global burden of CVDs need to take account of the modern epidemic in which heart failure, PAD and other chronic diseases are becoming more common than AMI and stroke. Male sex, older age, South Asian ethnicity and low social deprivation, although associated with many CVDs, are not associated with all, and this heterogeneity has implications for research into risk prediction, aetiology and prognosis Study 5: there was a discordance between incidence of SCAD, which was markedly higher among those of South Asian ethnicity than for those of white ethnicity, and prognosis which was significantly better in South Asians 36 Large-scale EHR cohort studies with detailed measures over time of clinical risk, and patient care identified through linkage of primary care, ACS registry, hospitalisation and cause-specific death data are warranted to better understand how South Asian ethnicity influences the onset and progression of coronary and other CVDs. Such studies will allow longitudinal patterns of risk and missed opportunities to lower risk before admission and after discharge to be evaluated In clinical trial design, selection of primary end points is crucial and should reflect the mechanism of action of the intervention and, where appropriate, the public health burden of CVDs in the 21st century.…”
Section: Electronic Health Records Data Opportunities In Coronary Dismentioning
confidence: 99%